Novel electrophysiological properties of dronedarone: inhibition of human cardiac two-pore-domain potassium (K2P) channels - Schmidt, Constanze; Wiedmann, Felix Tobias; Schweizer, Patrick Alexander; Becker, Rüdiger; Katus, Hugo; Thomas, Dierk (Naunyn-Schmiedeberg's archives of pharmacology, 2012)
Dronedarone is currently used for the treatment of paroxysmal and persistent atrial fibrillation (AF). Pharmacological inhibition of cardiac two-pore-domain potassium (K2P) channels results in action potential prolongation and has recently been proposed as novel antiarrhythmic strategy. We hypothesized that blockade of human K2P channels contributes to the electrophysiological efficacy of dronedarone in AF. Two-electrode voltage clamp and whole-cell patch clamp electrophysiology was used to record K2P currents from Xenopus oocytes and Chinese hamster ovary cells. All functional human K2P channels were screened for dronedarone sensitivity, revealing significant and concentration-dependent inhibition of cardiac K2P2.1 (TREK1; IC50 = 26.7 μM) and K2P3.1 channels (TASK1; IC50 = 18.7 μM) with maximum current reduction of 60.3 and 65.5 % in oocytes. IC50 values obtained from mammalian cells yielded 6.1 μM (K2P2.1) and 5.2 μM (K2P3.1). The molecular mechanism of action was studied in detail. Dronedarone block affected open and closed channels. K2P3.1 currents were reduced in frequency-dependent fashion in contrast to K2P2.1. Mutagenesis studies revealed that amino acid residues implicated in K2P3.1 drug interactions were not required for dronedarone blockade. The class III antiarrhythmic drug dronedarone targets multiple human cardiac two-pore-domain potassium channels, including atrial-selective K2P3.1 currents. K2P current inhibition by dronedarone represents a previously unrecognized mechanism of action that extends the multichannel blocking profile of the drug.